Behavioural Techniques in Work with Seniors - Botek, Ondrej; Kovalčíková, Nadežda (Magyar Gerontológia, 2025)
This article explores the application of storytelling as a cognitive-behavioural therapy (CBT) tool for older adults, emphasizing its effectiveness in illustrating the role of avoidance and exposure in anxiety recovery. Integrating a complete theoretical introduction and narrative case example with conceptual support from psychoeducational materials, the article demonstrates how storytelling facilitates therapeutic insight and engagement, particularly in older populations.